2009
DOI: 10.1111/j.1365-2656.2008.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing is everything: flexible phenology and shifting selection in a colonial seabird

Abstract: Summary 1.In order to reproduce successfully in a temporally varying environment, iteroparous animals must exhibit considerable behavioural flexibility across their lifetimes. By adjusting timing of breeding each year, parents can ensure optimal overlap between the energy intensive period of offspring production and the seasonal peak in favourable environmental conditions, thereby increasing their chances of successfully rearing young. 2. Few studies investigate variation among individuals in how they respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 61 publications
3
94
3
Order By: Relevance
“…Concurrently, hatching was progressively delayed at both colonies, in contrast to many other studies documenting that earlier breeding is a common response of seabirds to a warming climate (e.g. Moe et al 2009, Reed et al 2009, Votier et al 2009, Watanuki et al 2009). Delayed breeding parallel to increasing temperatures has, however, also been demonstrated for some seabird populations in both the northern (Frederiksen et al 2004, Moe et al 2009, Shultz et al 2009) and southern hemisphere (e.g.…”
Section: Discussioncontrasting
confidence: 90%
“…Concurrently, hatching was progressively delayed at both colonies, in contrast to many other studies documenting that earlier breeding is a common response of seabirds to a warming climate (e.g. Moe et al 2009, Reed et al 2009, Votier et al 2009, Watanuki et al 2009). Delayed breeding parallel to increasing temperatures has, however, also been demonstrated for some seabird populations in both the northern (Frederiksen et al 2004, Moe et al 2009, Shultz et al 2009) and southern hemisphere (e.g.…”
Section: Discussioncontrasting
confidence: 90%
“…Unfortunately, we lack data on the seasonal variation in food web components to estimate all the time lags involved. However, other studies on Farallon seabird phenology (Abraham & Sydeman 2004, Reed et al 2009, Wolf et al 2009) and seabird phenology elsewhere in the world (Frederiksen et al 2004, Barbraud & Weimerskirch 2006, Reed et al 2006 have inferred, rather than demonstrated, that environmental relationships are due to variation in prey resources. In short, it seems that wintertime upwelling 'pre-conditions' the system and is important to the growth and development of many prey species that are likely related to the foraging success, body condition, and timing of breeding for these seabirds.…”
Section: Ecosystem Pre-conditioningmentioning
confidence: 97%
“…Also, January through March is a very active period of fertilization/ parturition for some species of rockfish in the California Current (Eschevarria & Lenarz 1984). Reed et al (2009) used estimates of juvenile rockfish to show a relationship with murre phenology, although the forage fish data were obtained in May to June, after the egg-laying period of murres. Unfortunately, we lack data on the seasonal variation in food web components to estimate all the time lags involved.…”
Section: Ecosystem Pre-conditioningmentioning
confidence: 99%
“…The response of populations and species to climate change is strongly linked to ecological and evolutionary processes [9]. Such processes rely on genetic adaptation and/or phenotypic plasticity [10,11].…”
Section: Introductionmentioning
confidence: 99%